Pengenalan Pola Garis Telapak Tangan Menggunakan Metode Fuzzy K-Nearest Neighbor - Mahya Rudi Salim; Amrul Azizul Aziz Daulay; Glen Vier Sinaga (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Palm pattern recognition is an important topic in the field of pattern recognition and biometrics. This study aims to develop a palm line pattern recognition method using the Fuzzy K-Nearest Neighbor (Fuzzy KNN) method to improve the accuracy and effectiveness of the individual recognition system. The research was conducted by collecting images, performing segmentation, feature extraction, and implementing the Fuzzy KNN method. Based on the results of the experiments that have been carried out, it can be seen that the average accuracy obtained is 20%, which means that the system is less able to recognize palm line patterns. This is due to a lack of dataset which causes poor recognition performance on the model.